A new ice-core record from Lomonosovfonna, Svalbard:Viewing the 1920-97 data in relation to present climate and environmental conditions - Isaksson, E.; Pohjola, V.; Jauhiainen, T.; Moore, J.; Pinglot, J. F.; Vaikmäe, R.; Van De Wal, R. S.W.; Hagen, J. O.; Ivask, J.; Karlöf, L.; Martma, T.; Meijer, H. A.J.; et al. (2001)
In 1997 a 121 m ice core was retrieved from Lomonosovfonna, the highest ice field in Spitsbergen, Svalbard (1250 m a.s.l.). Radar measurements indicate an ice depth of 126.5 m, and borehole temperature measurements show that the ice is below the melting point. High-resolution sampling of major ions, oxygen isotopes and deuterium has been performed on the core, and the results from the uppermost 36 m suggest that quasi-annual signals are preserved. The 1963 radioactive layer is situated at 18.5-18.95 m, giving a mean annual accumulation of 0.36 m w.e. for the period 1963-96. The upper 36 m of the ice core was dated back to 1920 by counting layers provided by the seasonal variations of the ions in addition to using a constant accumulation rate, with thinning by pure shear according to Nye (1963). The stratigraphy does not seem to have been obliterated by meltwater percolation, in contrast to most previous core sites on Svalbard. The anthropogenic influence on the Svalbard environment is illustrated by increased levels of sulphate, nitrate and acidity. Both nitrate and sulphate levels started to increase in the late 1940s, remained high until the late 1980s and have decreased during the last 15 years. The records of δ 18 O, MSA (methanesulphonic acid), and melt features along the core agree with the temperature record from Longyearbyen and the sea-ice record from the Barents Sea at a multi-year resolution, suggesting that this ice core reflects local climatic conditions.